The Effectiveness of Roy’s Adaptation Model for Patients with Chronic Kidney Disease Undergoing Pre-Dialysis in Indonesia - Tri Hapsari Retno Agustiyowati; Ratna Sitorus; Agung Waluyo; Besral Besral (Jurnal Ners, 2018)
Introduction: Patients with chronic kidney disease (CKD) undergoing pre-dialysis requires a good self-management to control low protein intake and maintain kidney function. Adaptation to the existing stimulus through coping and adjustment mechanisms is important to maintaining good kidney function. However, few studies applied nursing theory based to guide intervention in helping the adaptation of patient CKD with their condition. The purpose of this study is to evaluate the effectiveness of Roy’s adaptation model towards physiological and psychological adaptation response among patients with CKD undergoing pre-dialysis.Methods: This study was conducted using a quasi-experiment to patients with CKD pre-dialysis, age over 18 years old. We modified Roy’s adaptation model for patients with CKD undergoing pre-dialysis.Results: A total of 70 subjects agreed to join the study, 38 subjects in intervention and 32 subjects in the control group. The mean of eGFR ranged from 26.3 to 26.6 mL/min/1.73 m2. We found that Roy’s adaptation model has significantly improved drinking behavior, reduce protein intake, blood creatinine, and psychosocial adaptation response after the intervention.Conclusion: These study findings suggested that Roy’s adaptation model is effective to help patients with CKD undergoing pre-dialysis improve their behavior and maintain kidneyfunction . Model dissemination, advocacy to related units, and application in nursing care in patients with chronic kidney disease pre-dialysis are necessary.